Answer :
Answer:
x = 4.5
y = -5
Step-by-step explanation:
2x - 3y = 24 2x + y = 4
y = -2x + 4
2x - 3(-2x + 4) = 24 y = -2(4.5) + 4
2x - (-6x + 12) = 24 y = -9 + 4
2x + 6x - 12 = 24 y = -5
8x - 12 = 24
8x = 36
x = 4.5
Answer:
x = 4 [tex]\frac{1}{2}[/tex] and y = -5
Step-by-step explanation:
2x-3y=24 --------------------------------------------------(1)
2x+y=4 ------------------------------------------------------(2)
We are to solve using substitution method.
From equation (2),
2x + y = 4
subtract 2x from both-side of the equation
2x - 2x + y = 4 - 2x
y = 4 - 2x ------------------------------------------------(3)
Substitute equation (3) in equation (1)
2x-3y=24
2x - 3(4 - 2x) = 24
2x - 12 + 6x = 24
8x - 12 = 24
Add 12 to both-side of the equation
8x - 12 + 12 = 24 + 12
8x = 36
Divide both-side of the equation by 8
8x/8 = 36/8
x = 9/2 = 4 [tex]\frac{1}{2}[/tex]
Substitute x = 9/2 in equation (3) to get the value of y
y = 4 - 2x
= 4 - 2([tex]\frac{9}{2}[/tex])
= 4 - 9
= -5
y = -5
x = 4 [tex]\frac{1}{2}[/tex] and y = -5